2022
DOI: 10.3389/fnins.2022.972658
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cingulate cortex and its projections to the ventral tegmental area regulate opioid withdrawal, the formation of opioid context associations and context-induced drug seeking

Abstract: Clinical evidence suggests that there are correlations between activity within the anterior cingulate cortex (ACC) following re-exposure to drug-associated contexts and drug craving. However, there are limited data contributing to our understanding of ACC function at the cellular level during re-exposure to drug-context associations as well as whether the ACC is directly related to context-induced drug seeking. Here, we addressed this issue by employing our novel behavioral procedure capable of measuring the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 132 publications
0
7
0
Order By: Relevance
“…Following oxycodone IVSA, measures of spontaneous withdrawal-related aggression and hyperalgesia have been reported 12 h after the last IVSA session 48 . Spontaneous SSW have also been observed following oral oxycodone intake in mice, when examined 24 h after the last oral intake session 49 .…”
Section: Discussionmentioning
confidence: 96%
“…Following oxycodone IVSA, measures of spontaneous withdrawal-related aggression and hyperalgesia have been reported 12 h after the last IVSA session 48 . Spontaneous SSW have also been observed following oral oxycodone intake in mice, when examined 24 h after the last oral intake session 49 .…”
Section: Discussionmentioning
confidence: 96%
“…The dose and duration of oral oxycodone access are important differences when comparing results between oral oxycodone studies. Using different experimental protocols of oral oxycodone, other studies have reported that mice and rats escalate oral oxycodone intake across sessions (Zanni et al ., 2020; McKendrick et al ., 2022; Slivicki et al , 2023). For example, Zanni and co-workers (2020) had rats consume oxycodone orally for 22 weeks, whereas in the current study and in the study by Iyer et al .…”
Section: Discussionmentioning
confidence: 99%
“…For oral intake experiments, mice received drinking water with oxycodone (0.5 mg/ml) or drinking water without oxycodone in their home cage bottle for 10 consecutive days ( n = 12 per group, six males/six females). The concentration of oxycodone used in the drinking water was based on previous studies (Phillips et al ., 2020; McKendrick et al ., 2022; Slivicki et al ., 2023). No taste adulterants were added to the water or oxycodone solutions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 1 ng of CTAP was used based on a previous publication ( Simmons and Self, 2009 ). For DREADD experiments, CNO (3 µm, 300 nl) was injected into the PVT at an infusion rate of 300 nl/min as we have shown that this concentration of CNO is sufficient to activate hM4D(Gi)-DREADDs ( McKendrick et al, 2022 ) and others have shown that 3 µm CNO is sufficient to activate hM4D(Gi)-DREADDs in the PVT ( Keyes et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%